2005
DOI: 10.1103/physrevb.72.085451
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-induced magnetism in carbon nanotubes

Abstract: Spin-polarized density functional theory is used to investigate hydrogen-induced magnetism in single-walled carbon nanotubes ͑SWNTs͒. Hydrogen trapped at a carbon vacancy can trigger delocalized electron spin polarization on semiconducting zigzag SWNTs. Hydrogen pinned by a carbon adatom on the surface of the SWNT can induce spin polarization localized at the carbon adatom, independent of the diameter and chirality of the tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 38 publications
5
58
1
Order By: Relevance
“…Therefore, it is important to study the possible magnetism of graphene to understand magnetism in other carbon allotropes. Nonmagnetic-defect-induced magnetism in graphene has also been reported using first-principles calculations [16][17][18][19][20][21][22][23][24]. We have also studied the problem using a tight-binding model, and also found nonmagnetic-defect-induced magnetism in graphene [22,[26][27][28]31].…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, it is important to study the possible magnetism of graphene to understand magnetism in other carbon allotropes. Nonmagnetic-defect-induced magnetism in graphene has also been reported using first-principles calculations [16][17][18][19][20][21][22][23][24]. We have also studied the problem using a tight-binding model, and also found nonmagnetic-defect-induced magnetism in graphene [22,[26][27][28]31].…”
Section: Introductionmentioning
confidence: 87%
“…While the origin of magnetic ordering in such systems is yet to be fully understood, it has been suggested that spin polarization may arise from local structural defects, 33,36,41,53 sterically protected carbon radicals 34 and chemical impurities. 30,40,43 A unique mechanism for spin ordering in graphene based systems is related to the appearance of edge states. [18][19][20][21][22][23][24][25][26][27][28][29]42,[45][46][47][48][49][50][51][52] When cutting a graphene sheet along its zigzag axis to form a narrow and elongated graphene nanoribbon (GNR), distinct electronic states appear, which are localized around the exposed edges.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, the hydrogenation treatment of carbon materials can also induce magnetism. [11][12][13] These theoretical studies provide useful theoretical guide for the experimental synthesis of these metal-free magnetic materials, which, however, remain challenging partially due to the difficulties in the controlled growth of these defects.…”
Section: Fluorination-induced Magnetism In Boron Nitride Nanotubes Frmentioning
confidence: 99%